Characterization of input materials to provide an estimate of mercury emissions related to China's cement industry. (1st February 2021) - Cui, Jingxuan; He, Jie; Xiao, Ying; Li, Juan; Di, Yang
Abstract: In the cement production process, in addition to conventional pollutants (such as particulate matter, NOX and SO2 ), heavy metal pollutants including mercury are also emitted. Globally, the cement industry is one of the most important sources of atmospheric mercury. China's cement production accounts for 50% of global cement production. To obtain a more detailed inventory of atmospheric mercury emissions from China's cement industry, a total of 344 solid samples (limestone: 79; coal: 78; corrective materials: 131; and clinker: 56) from 60 production lines in 23 provinces and cities nationwide were collected and tested. Using statistical analysis, the best estimates of the mercury concentrations of limestone, coal, corrective materials and clinker were 0.047 mg/kg, 0.141 mg/kg, 0.061 mg/kg and 0.011 mg/kg. Thus, we estimated that the annual input of mercury is 132 t/a. Based on the principle of conservation of mass, the atmospheric mercury emissions from the cement industry in 2015 were estimated to be 118 t/a, yielding an emission factor of 0.091 g/t clinker. These data improve the accuracy of the atmospheric mercury emission inventory related to the cement industry and support development of mercury control technologies in China. Highlights: Emissions value is 118 tHg, accounting for 89% of the input. Emission factor is 0.091g/t clinker. Tested 344 samples.